Boosting MSME Performance and Competitive Advantage Through Strategy and Innovation: Insights From Malang City - Aisyah, Nabila Nur; Arif, Moh. Erfan (Jurnal Kewirausahaan dan Inovasi, 2025)
MSME is one of the most vital industrial sectors in Indonesia’s economy, serving as a key driver of economic activity across various fields. With the increasing number of its units, competition among businesses has become more intense, potentially leading some enterprises to exit the market. Therefore, they must possess competitive advantages to survive and grow. Several researchers have stated that competitive advantage can be influenced by business strategy, innovation, and performance. This study aims to examine the influence of business strategy and innovation on competitive advantage among MSMEs in Malang City with performance as a mediating variable. Here Partial Least Squares was used to assess the inner and outer models, and hypothesis testing was conducted; both were performed using SmartPLS. This study finds that: (1) business strategy significantly influences competitive advantage; (2) innovation does not significantly affect competitive advantage; (3) business strategy has a significant impact on performance; (4) innovation significantly affects performance; (5) performance has a notable impact on competitive advantage; (6) business strategy has a significant and positive indirect influence on competitive advantage through performance; and (7) innovation significantly and negatively influences competitive advantage through performance.